Eco-friendly freestanding superhydrophobic thin films and coatings for corrosion protection - Junaid Saleem (14670322) (2024)
Superhydrophobic surfaces and coatings have gained significant attention for their potential in anti-corrosion applications, yet they present several challenges. These coatings typically lack the flexibility to function as freestanding films, limiting their ease of application and removal. Additionally, existing techniques often involve complex chemical processes and utilize materials that are costly and environmentally hazardous. In this study, waste polyethylene is valorized to produce flexible superhydrophobic films and coatings with anticorrosive properties. The process employs thermally induced phase separation using a bio-solvent and spin-casting. The resulting films demonstrate dual functionality as both anti-corrosion coatings and freestanding films. The maximum contact angle of anticorrosive film was found to be 148o. The maximum charge transfer resistances Rct of carbon steel and polymer coated film were 0.184 and 173 kΩ.cm2, respectively. The electrochemical impedance spectrometry (EIS) shows a corrosion inhibition efficiency of 99.39%, which confirms the superior anticorrosive properties of the coating. Importantly, the use of waste polyethylene offers a cost-effective and environmentally friendly solution to conventional superhydrophobic coatings, contributing to the circular economy and reducing plastic waste. Overall, this study presents an alternate strategy to develop anticorrosive superhydrophobic films, providing a template for utilizing waste polyethylene in corrosion protection applications. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42247-024-00794-y